SUPPORTIVE EDUCATIVE TERHADAP PENGETAHUAN SELF CARE DAN SELF EFFICACY PASIEN PENYAKIT PARU OBSTRUKTIF KRONIK - Nita Arisanti Yulanda; Mita Mita (Akademi Keperawatan Dharma Husada Kediri, 2020)
Introduction: Supportive educative system is a nursing practice with the aim of providing education and support the patients COPD able to perform self-care independently. The purpose of this research is to analyze the influence supportive education on self-care independence. Method: This research used experimental design of pre-post test control group design. The sample size was 32 patients: 16 COPD patients at Soedarso - Pontianak General Hospital and 16 patients of dr. Abdul Aziz – Singkawang General Hospital. The variables of this research are supportive educative, self-care knowledge, and self-efficacy. Data collection using questionnaires and analyzed by paired t-test and simple linear regression. Result: The results showed a supportive educative effect on self-care independence. The result of paired t-test is significant difference in the intervention group that is self-care knowledge, and self-efficacy. While in the control group was not significant. The result of the regression test of supportive educative has an effect on the variable of self-care knowledge (R square 0,409) and insignificant in self-efficacy (R square 0,000). Discussion: Teaching and guiding methods in supportive educative programs can have an impact on aspects of nutritional patterns, especially improving eating habits, on the contrary to self-efficacy of the elderly not because they are more likely to focus on acceptance and rejection of their abilities in line with physical and intellectual setbacks.